PENERAPAN METODE CREATIVE PROBLEM SOLVING DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIIIC SMP NEGERI 11 MERANGIN - Mahniar Siregar (Fokus | Jurnal Pendidikan STKIP YPM Bangko, 2022)
This research is motivated by the low learning outcomes obtained by students. The average student learning outcomes have not reached the specified KKM, which is 75. One solution to fix these problems is to apply the Creative Problem Solving learning model. With the application of this learning model, it is expected that students' mathematics learning outcomes will increase. This research is a Classroom Action Research (CAR) which was carried out in 2 cycles, with the steps of each cycle consisting of planning, action, observation and evaluation and reflection. Subjects and objects of research were 37 students of class VIIIC, using the Creative Problem Solving learning model. The instrument used to obtain student learning outcomes and activities is a test sheet consisting of 5 questions and an observation sheet. Learning outcomes data were analyzed using the average percentage technique. Based on the results of the study, it was found that on average there was an increase in student learning outcomes from each cycle. The average learning outcome in the first cycle was 72.14 with the percentage of students who completed 67.57% an increase in the second cycle, namely the average student learning outcome was 78.78, with the percentage of students who completed classically reached 86.49%.